THE RESPONSE OF THIRD GRADE IN SD NEGERI KLEPU TOWARD POP UP BOOK TEACHING THEME 7 SUBTHEME 1 TECHNOLOGY DEVELOPMENT - Yuni Ana Anjarwati; Dwi Kameluh Agustina; Sripit Widiastuti (Universitas Islam Balitar, 2019)
Based on the results of the study in an elementary school with observations,Lack of thematic learning media, less attractive presentation of text books. To overcome these problems, the need for media that can support the students in learning. The media is the media puberty. Also the media pubescent see two and three-dimensional shape. This research is descriptive research. The purpose of this study was to describe the student's response to the Pop-Up Book For Learning Theme 7 Subtheme 1 Technology developments.Results of the study pubescent development is the acquisition of the validation results of the expert content of 94%, and 87% of media experts, from both the results of this validation media entered puberty at a very decent qualifications do not need to be revised. Thus, pubescent product fit for use as a medium of learning theme 7 subthemes 1 to Class III SD. Based on the results of the acquisition of the response of learners to answer the attractiveness response gets a percentage of 91.2% and an answer to 92.00% in terms of understanding the material. From these results it can be concluded that the media instructional simulation pubescent get a positive response from the students and can be used as a medium of learning theme 7 subthemes 1 to Class III SD.